Peak power output test on a rowing ergometer: A methodological study - Metikos, B.; Mikulic, P.; Sarabon, N.; Markovic, G. (The Journal of Strength and Conditioning Research, 2015)
We aimed to examine the reliability and validity of the peak power output test on a rowing ergometer (Concept II Model D Inc.) and to establish the "optimal resistance" at which this peak power output was observed in 87 participants with varying levels of physical activity and rowing expertise: 15 male and 12 female physically inactive students (age: 21 ± 2 years), 16 male and 20 female physically active students (age: 23 ± 2 years), and 15 male and 9 female trained rowers (age: 19 ± 2 years). The participants performed countermovement jump (CMJ) test on a force plate, followed by 3 maximal-effort rowing trials using the lowest, medium, and the highest adjustable resistance settings (i.e., "1", "5," and "10" on the resistance control dial on the ergometer) in randomized order. The test proved to be reliable (coefficients of variation: 2.6-6.5%; intraclass correlation coefficients: 0.87-0.98). The correlation coefficients between CMJ peak power and rowing peak power (both in watts per kilogram) were fairly consistent across all 3 groups of participants and resistance levels, ranging between r = 0.70 and r = 0.78. Finally, the highest power output was observed at the highest resistance setting in 2 nonathletic groups (p < 0.01), whereas rowers seem to produce the highest power output at the moderate-resistance setting. We conclude that the power output test on a Concept II rowing ergometer may serve as a reliable and valid tool for assessing whole-body peak power output in untrained individuals and rowing athletes.